2016
DOI: 10.1038/pr.2016.244
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in the transcription factor FOXF1 cosegregating with infantile hypertrophic pyloric stenosis in the extended pedigree linked to IHPS5 on chromosome 16q24

Abstract: A novel missense mutation in the transcription factor FOXF1 co-segregating with infantile hypertrophic pyloric stenosis in the extended pedigree linked to IHPS5 on chromosome 16q24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Structural variation affecting FOXF1 is associated with CHDs 33 and a recent study of familial IHPS identified a FOXF1 missense mutation segregating with disease trait in an extended pedigree with eight IHPS cases. 34 Further studies are, however, clearly required to illuminate possible common regulatory mechanisms involved in IHPS and CHD pathogenesis. Even if some etiological factors are confirmed to be shared between IHPS and CHD, it is important to emphasize that both conditions are very heterogeneous and are influenced by other environmental and genetic factors that are not shared.…”
Section: Discussionmentioning
confidence: 99%
“…Structural variation affecting FOXF1 is associated with CHDs 33 and a recent study of familial IHPS identified a FOXF1 missense mutation segregating with disease trait in an extended pedigree with eight IHPS cases. 34 Further studies are, however, clearly required to illuminate possible common regulatory mechanisms involved in IHPS and CHD pathogenesis. Even if some etiological factors are confirmed to be shared between IHPS and CHD, it is important to emphasize that both conditions are very heterogeneous and are influenced by other environmental and genetic factors that are not shared.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous SNVs in the FOXF1 gene on chromosome 16q24.1 or CNV deletions involving FOXF1 (MIM# 601089) and/or its distant lung-specific enhancer, located ~286 kb upstream, are found in 80%-90% of patients with ACDMPV. To date, more than 64 distinct pathogenic or likely pathogenic SNVs (missense and nonsense), 29 indels (frameshift) and 70 CNV deletions have been reported (Abu-El-Haija et al, 2018;Everett et al, 2017;Hayasaka et al, 2018;Ma et al, 2017;Nagano et al, 2016;Pradhan et al, 2019;Sen et al, 2013;Stankiewicz et al, 2009;Szafranski et al, 2013Szafranski et al, , 2014Szafranski et al, , 2016Szafranski et al, , 2019Szafranski et al, , 2022Yildiz Bolukbasi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV, MIM# 265380) is a rare neonatal developmental lung disease, lethal due to severe respiratory distress and refractory pulmonary hypertension (PAH) (Bishop, Stankiewicz, & Steinhorn, 2011). To date, more than 70 distinct ACDMPV-related FOXF1 heterozygous point mutations and 60 copy-number variant (CNV) deletions involving FOXF1 and/or its upstream lung-specific enhancer at 16q24.1 have been identified in 80–90% of ACDMPV patients (Abu-El-Haija et al, 2018; Everett, Ataliotis, Chioza, Shaw-Smith, & Chung, 2017; Hayasaka et al, 2018; Ma et al, 2017; Nagano, Yoshikawa, Hosono, Takahashi, & Nakayama, 2016; Pradhan et al, 2019; Sen, Gerychova, et al, 2013; Stankiewicz et al, 2009; Szafranski et al, 2013, 2014, 2016). FOXF1 (Forkhead box F1, MIM#601089) encodes a transcription factor of the fork-head family, and is regulated by the sonic hedgehog (SHH) signaling pathway during lung development (Fernandes-Silva, Correia-Pinto, & Moura, 2017; Kalinichenko et al, 2001).…”
Section: Introductionmentioning
confidence: 99%